Droplet bouncing on the surface with micro-structure - Bobinski, T.; Sobieraj, G.; Psarski, M.; Celichowski, G.; Rokicki, J. (Archives of Mechanics, 2017)
In this paper, we present static and dynamic interactions of water droplets with a micro-structured surface that exhibits hydrophobic properties. Droplets with two different diameters (D0 = 0.6 ± 0.1 mm and D0 = 2.6 ± 0.1 mm) were studied for impact velocities in the range of 0.1 ÷ 2.5 m/s. This allowed to investigate the influence of gravity on the collision behavior during an impact. The main result of the present research is the determination of the critical conditions for consecutive transitions leading to various scenarios of droplet rebound for each of the investigated surface geometry.